Strengthening the contribution of aquaculture to food and nutrition security: The potential of a vitamin A-rich fish in Bangladesh - Fiedler, John L.; Lividini, Keith; Drummond, Elizabeth; Thilsted, Shakuntala H. (Elsevier, 2016)
Since 1961, global per capita fish consumption has nearly doubled. Much of the increase has been due to aquaculture. Bangladesh, the world's eighth largest fish producing country, has been part of this transformation. Despite having vitamin A supplementation and fortification programs, the prevalence of inadequate vitamin A intake (IVAI) in Bangladesh is very high, estimated to be 60%. The promotion of a small indigenous fish, high in vitamin A – mola carplet – offers a promising food-based approach to improving vitamin A status of the 98% of Bangladeshis who eat fish. The objective of this paper was to conduct a benefit–cost analysis of a national household pond Mola Promotion Program (MPP) in Bangladesh. Using the 2005 Bangladesh Household Income and Expenditure Survey (HIES) and nutrition and health statistics, we developed baseline estimates of usual vitamin A intake, the prevalence of IVAI and disability-adjusted life years (DALYs) attributable to vitamin A deficiency (VAD). Drawing on a WorldFish project and HIES data, we designed and modeled the implementation of a MPP, and calculated the additional vitamin A intake it would provide, calculated new incidence rates of VAD-related health outcomes and estimated MPP-attributable annual changes in DALYs. The MPP's total health benefits were calculated over the program's 11-year phase-in as the annual sum of DALYs saved. The MPP's costs were estimated as the sum of the costs of a small fish program of the Fisheries Development Program plus the costs of mola brood stock, other inputs and additional farmer training-related costs. Program costs and benefits were combined to produce estimates of the cost-effectiveness of the program. An 11-year, $23 million project would increase average daily vitamin A intakes by 7 μg retinol activity equivalent (RAE), reduce the prevalence of IVAI by 1.1 percentage points, and save 3000 lives and 100,000 DALYs, at a cost of $194 per DALY saved. The MPP's impact would be concentrated among homestead pond-fishing households that would consume 60% of the additional mola produced. Among these, it would reduce IVAI prevalence by 7 percentage points. If the MPP was implemented for at least 20 years, it would dominate – have higher health benefits and lower total costs – than a national vitamin A wheat flour fortification program. By World Bank and World Health Organization criteria, the MPP is a cost-effective approach to reduce the burden of micronutrient malnutrition in Bangladesh.